An improved combustion apparatus for the determination of organically bound tritium in environmental samples. (April 2016) - Du, Lin; Shan, Jian; Ma, Yu-Hua; Wang, Ling; Qin, Lai-Lai; Pi, Li; Zeng, You-Shi; Xia, Zheng-Hai; Wang, Guang-Hua; Liu, Wei
Abstract: This paper reports an improved combustion apparatus for the determination of organically bound tritium in environmental samples. The performance of this apparatus including the recovery rate and reproducibility was investigated by combusting lettuce and pork samples. To determine the factors for the different recovery rates of lettuce and pork and investigate whether the samples were completely oxidized, the ashes and exhaust gases produced by the combustion were analyzed. The results indicate that the apparatus showed an excellent performance in the combustion of environmental samples. Thus, the improvements conducted in this study were effective. Highlights: Three major improvements were made to develop the combustion apparatus for OBT. The recovery is higher and more stable than that of current equipment. Little hydrogen was present in the ashes and exhaust after combustion.